Oase des Glücks Gedanken zu einer Ontologie des Spiels - Fink, Eugen (Interpretationen und Quellen, 2023)
One of Eugen Fink's most important texts is "Oasis of Happiness. Thoughts on an Ontology of Play". Against the background of the interest in the phenomenon of play in philosophy and the social and cul-tural sciences, the Freiburg philosopher develops in this book an independent and innovative approach to play and playing, which is likely to prove a classic of 20th century philosophy. This volume on Fink's "Oasis of Happiness" contains not only this fundamental text, but also numerous interpretations from leading Fink scholars. It introduces not only Fink's reflections on play, but also methodologically his genuine phenomenological approach, and shows the broad international reception